The direct measurement of the electronic density of states of graphene using metastable induced electron spectroscopy. (10th April 2017) - Chambers, Benjamin A; Neumann, C; Turchanin, Andrey; Gibson, Christopher T; Andersson, Gunther G
Abstract: Graphene single and multilayers were investigated for the first time with metastable induced electron spectroscopy (MIES). MIES is only sensitive to the electronic structure of the outermost layer and thus the substrate does not contribute to the spectra. It has been shown that the electronic structure of graphene changes with the number of layers and can be correlated to the band structure calculations. Angle resolved x-ray photoelectron spectroscopy in combination with Raman spectroscopy were employed to determine the thickness and the structure of the graphene samples and their defect density. We demonstrate that MIES can be used to measure directly the electronic density of states in graphene samples, which correlates to their structural characteristics such as number of layers and presence of defects.